Effects of Different LED Light Quality Combinations on Nutritional Quality and Physiological Characteristics of Celery - Kaiyue Liu; Li Tang; Qianwen Chu; Yingyi Lu; Lihong Su; Shaobo Cheng; Zhongqun He; Xiaoting Zhou (Horticulturae)
Light is essential for vegetable growth, with varying combinations of light quality affect differently on plant growth and development. In order to clarify the optimal light quality combination of celery LEDs, under hydroponic and full LED light conditions, this study investigated distinct combinations of light quality have various impacts on the growth and quality of celery using “Hongcheng Red Celery” as test material. Red-blue (R:B = 3:1, control), red-blue-purple (R:B:P = 3:1:1, purple (P)), red-blue-green (R:B:G = 3:1:1, green (G)), red-blue-yellow (R:B:Y = 3:1:1, yellow (Y)), and red-blue-far-red (R:B:FR = 3:1:1, far-red (FR)) light conditions were set up in the experiment, and plants were treated for 45 days. The findings indicated that the best growth in celery was achieved under the RBP, while RBG inhibited the growth of celery. The chlorophyll a and total chlorophyll contents of celery leaves were increased significantly by the RBP treatments compared to RB. In addition, net photosynthetic rate, stomatal conductance, and transpiration rate were highest in RBP. In RBP treatment, soluble protein, vitamin C, total phenols, total flavonoids, Ca, Fe, Zn in leaves and petioles of celery were higher than in other treatments. And the anthocyanins content in celery petioles was higher than other treatments. The RBP and RBG treatments reduced nitrate content. The RBP treatment increased the activities of apigenin synthesis-related enzymes CHS, FNS, ANS, and up-regulated expression of related genes CHS, FNS, and ANS, and increased apigenin content. In summary, the RBP is more favorable for celery growth and nutrient synthesis.